Frontal Hemodynamic Responses to High Frequency Yoga Breathing in Schizophrenia: A Functional Near-Infrared Spectroscopy Study - Bhargav, Hemant; BN, Gangadhar; Raghuram, Nagarathna; HR, Nagendra (Frontiers in Psychiatry, 2014)
Frontal hemodynamic responses to high frequency yoga breathing technique, Kapalabhati (KB), were compared between patients of schizophrenia (n = 18; 14 males, 4 females) and age, gender, and education matched healthy subjects (n = 18; 14 males, 4 females) using functional near-infrared spectroscopy. The diagnosis was confirmed by a psychiatrist using DSM-IV. All patients except one received atypical antipsychotics (one was on typical). They had obtained a stabilized state as evidenced by a steady unchanged medication from their psychiatrist for the past 3 months or longer. They learned KB, among other yoga procedures, in a yoga retreat. KB was practiced at the rate of 120 times/min for 1 min. Healthy subjects who were freshly learning yoga too were taught KB. Both the groups had no previous exposure to KB practice and the training was carried out over 2 weeks. A chest pressure transducer was used to monitor the frequency and intensity of the practice objectively. The frontal hemodynamic response in terms of the oxygenated hemoglobin (oxyHb), deoxygenated hemoglobin (deoxyHb), and total hemoglobin (totalHb) or blood volume concentration was tapped for 5 min before, 1 min during, and for 5 min after KB. This was obtained in a quiet room using a 16-channel functional near-infrared system (FNIR100-ACK-W, BIOPAC Systems, Inc., USA). The average of the eight channels for each side (right and left frontals) was obtained for the three sessions. The changes in the levels of oxyHb, deoxyHb, and blood volume for the three sessions were compared between the two groups using independent samples t-test. Within group comparison showed that the increase in bilateral oxyHb and totalHb from the baseline was highly significant in healthy controls during KB (right oxyHb, p = 0.00; left oxyHb, p = 0.00 and right totalHb, p = 0.01; left totalHb, p = 0.00), whereas schizophrenia patients did not show any significant changes in the same on both the sides. On the other hand, schizophrenia patients showed significant reduction in deoxyHb in the right pre-frontal cortex (right deoxyHb, p = 0.00). Comparison between the groups showed that schizophrenia patients have reduced bilateral pre-frontal activation (right oxyHb, p = 0.01; left oxyHb, p = 0.03 and right total Hb, p = 0.03; left total Hb, p = 0.04) during KB as compared to healthy controls. This hypo-frontality of schizophrenia patients in response to KB may be used clinically to support the diagnosis of schizophrenia in future.